Morphology Effect of Anodized TiO2 Nanotubes Active Anodes on Dye Sensitive Solar Cell - Ali Alsammarraie, Abdulkareem Mohammed; Jawad, Mohammed Kadhim (Asian Journal of Chemistry, 2017)
Anodized TiO2 nanotubes have recently became one of the favourable active anodes in making dye sensitive solar cell. This work investigate the effect of morphological properties of the anodized TiO2 on the electrical conversion efficiency (h %) of the dye sensitive solar cells fabricated using N3 commercial dye, polymers blend (KI/PEO/PMMA) as electrolyte and electro-polymerized polyaniline on fluorine-doped tin oxide glass as counter electrode. Different morphological TiO2 were produced via anodizing of the Ti foil in ethylene glycol containing 0.5 % NH4F and 4 mL deionized water, at different anodizing potentials; namely 10, 20, 30, 40, 50 and 60 v for 1 h at room temperature. The deposited anodized TiO2 nanotubes layers extensively characterized using scanning electron microscope. The calculated (h %) ranged between 0.370 and 2.126 %, the relation between these values and the tubes parameters were discussed.